Select the best: Positive selection to improve farm saved seed potatoes: Farmer field aid - Gildemacher, P. (CTA / International Potato Center, 2009)
Intended as a reference for farmers trained in seed potato selection and to promote farmer-to-farmer technology transfer, this full-colour leaflet outlines the basic principles of seed potato selection and includes photographs depicting the major potato diseases. It accompanies the Trainers Manual and the Picture Book (see 1538 and 1541).